Clinically Important Features of Porphyrin and Heme Metabolism and the Porphyrias - Siddesh Besur; Wehong Hou; Paul Schmeltzer; Herbert L. Bonkovsky (Metabolites, 2014)
Heme, like chlorophyll, is a primordial molecule and is one of the fundamental pigments of life. Disorders of normal heme synthesis may cause human diseases, including certain anemias (X-linked sideroblastic anemias) and porphyrias. Porphyrias are classified as hepatic and erythropoietic porphyrias based on the organ system in which heme precursors (5-aminolevulinic acid (ALA), porphobilinogen and porphyrins) are chiefly overproduced. The hepatic porphyrias are further subdivided into acute porphyrias and chronic hepatic porphyrias. The acute porphyrias include acute intermittent, hereditary copro-, variegate and ALA dehydratase deficiency porphyria. Chronic hepatic porphyrias include porphyria cutanea tarda and hepatoerythropoietic porphyria. The erythropoietic porphyrias include congenital erythropoietic porphyria (Gűnther’s disease) and erythropoietic protoporphyria. In this review, we summarize the key features of normal heme synthesis and its differing regulation in liver versus bone marrow. In both organs, principal regulation is exerted at the level of the first and rate-controlling enzyme, but by different molecules (heme in the liver and iron in the bone marrow). We also describe salient clinical, laboratory and genetic features of the eight types of porphyria.